Klasifikasi Jumlah Daun pada Semai Hidroponik menggunakan Pengolahan Citra dan Jaringan Syaraf Tiruan berbasis Raspberry Pi - Ahmad Wildan Farras Mumtaz; Hurriyatul Fitriyah; Fitri Utaminingrum (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2022)
Hydroponics is a technique of growing crops without using soil as a growth medium. A plant that is often cultivated and applied to hydroponic practices and has a relatively fast harvest period is mustard pakcoy(Brassica rapa subsp. chinensis). To produce healthy and quality mustard pakcoy, monitoring is needed, especially during the seeding period for Â±21 days. When the seedling period is over, the plant must be removed immediately so that it does not quickly age and inhibit vegetative growth. In this study, an automatic monitoring system for the number of mustard pakcoy leaves was designed. This system utilizes image processing and uses a raspberry pi-based Artificial Neural Network method in its manufacture. The mustard leaf image will be captured using a webcam camera which will then be processed into a raspberry pi and the detection results will be displayed on a 16x2 i2C LCD. The training data used in this study were 300 data. The results of 40 tests carried out by this monitoring system get an accuracy of 92.5% with a system computing time of 4.6445 seconds and a computation time of the ANN method 1.2185 seconds.